Regulation of abscisic acid metabolism in relation to the dormancy and germination of cereal grains - Justyna Fidler; Edyta Zdunek-Zastocka; Wiesław Bielawski (Acta Societatis Botanicorum Poloniae, 2015)
Seed dormancy is of particular importance in the cultivation of cereals, as it directly affects the quality of crop yield. If the dormancy period is too short, this may lead to pre-harvest sprouting, whereas a dormancy period that is too long may cause uneven germination; both of these scenarios are associated with economic losses. Most enzymes engaged in the metabolism of abscisic acid (ABA) have been identified, and significant progress has been made in understanding the role of this phytohormone in the induction and maintenance of dormancy, mainly as a result of research conducted in Arabidopsis. Much less is known about the metabolism and function of ABA in cereal grains, especially in relation to dormancy and germination. This review focuses on the regulation of ABA metabolism in dormant and non-dormant cereal grains, in both the dry state and upon imbibition. Moreover, this review describes the influence of factors such as after-ripening, light, temperature, nitric oxide, and reactive oxygen species (ROS) on the dormancy and germination of cereal grains. These factors, with the exception of ROS, appear to affect the level of dormancy and germination of grains through regulation of ABA metabolism.